Management of Research and Innovation Projects under the Triple Helix Model - Valencia Achuri, Paola Andrea; Taboada Álvarez, Jorge Enrique (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2022)
The model known as the Triple Helix (Government, University, Industry/Society), promotes the development of a country through research and innovation. Currently there is no review on the relationship and interaction between the actors of the model, focused on the management of CTeI projects. This exploratory article allows an approach to the management of CTeI projects under the model, presenting the theoretical references on the interactions, results and benefits of cooperation between the actors, followed by a review of methodologies and knowledge frameworks in project management. projects applied in CTeI projects.